Steady and unsteady Magnetohydrodynamics (MHD) boundary layer flows and heat transfer over stretching surfaces / Zanariah Mohd Yusof - Mohd Yusof, Zanariah (2014)
Study on the influence of the magnetic field, radiation and porous medium on the heat transfer is very important in controlling the problems that occur in industrial manufacturing processes and a final product of desired characteristics can be achieved. In this study, three problems of boundary layer are discussed. The Problem 1 considered is a steady two-dimensional boundary layer flow over a vertical surface in an incompressible, viscous and electrically conducting fluid in the presence of a transverse magnetic field and thermal radiation embedded in porous media over a linearly stretching surface while the Problem 2 focused towards an exponentially stretching surface. The Problem 3 analyzed the radiation effects on unsteady magnetohydrodynamics (MHD) flow over a linear stretching surface. The governing partial differential boundary layer equations are first transformed into ordinary differential equations by using similarity transformations. The ordinary differential equations for the first two problems are solved numerically by a finite difference method known as Keller-box Method. Numerical solutions for the third problem are obtained by employing the Runge-Kutta-Fehlberg method with shooting technique. The results presented includes the effects of Prandtl number, Eckert number, magnetic parameter, radiation parameter, permeability parameter and unsteadiness parameter on the velocity and temperature profiles, the skin friction and heat transfer coefficient. It is found that the heat transfer rate at the surface increases as the Prandtl number and unsteadiness parameter increase but decreases with magnetic, permeability and radiation parameter.